2015
DOI: 10.11646/zootaxa.4034.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in the Mexican endemic Rufous-backed Robin, <br />Turdus rufopalliatus (Passeriformes: Turdidae)

Abstract: The Rufous-backed Robin (Turdus rufopalliatus) is endemic to deciduous and semideciduous tropical forests of western Mexico. Of the currently recognized subspecies, T. r. graysoni, from the Tres Marías Islands and nearby coastal Nayarit, has been considered a separate species; however, this treatment has been challenged due to an apparent contact zone on the mainland, although no hybrids have ever been recorded. Here, we use mitochondrial DNA sequences from individuals sampled across the species' range to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Morphometrics.-Larger in all external measurements, especially tarsus length and bill length (score 2). Montaño-Rendón et al (2015), based on 268 adult specimens from throughout the range of T. rufopalliatus (sensu lato), confirmed the existence of marked morphometric differences.…”
Section: Rufous-backed Robin Turdus Rufopalliatus Graysoni (Vs T R Rufopalliatus)mentioning
confidence: 59%
See 3 more Smart Citations
“…Morphometrics.-Larger in all external measurements, especially tarsus length and bill length (score 2). Montaño-Rendón et al (2015), based on 268 adult specimens from throughout the range of T. rufopalliatus (sensu lato), confirmed the existence of marked morphometric differences.…”
Section: Rufous-backed Robin Turdus Rufopalliatus Graysoni (Vs T R Rufopalliatus)mentioning
confidence: 59%
“…Additional information. -Montaño-Rendón et al (2015) and Ortiz-Ramírez et al (2018) found reciprocal monophyly and deep genetic divergence between graysoni and rufopalliatus.…”
Section: Rufous-backed Robin Turdus Rufopalliatus Graysoni (Vs T R Rufopalliatus)mentioning
confidence: 99%
See 2 more Smart Citations
“…En cuanto a endemismos e identidad biológica mexicana, la riqueza de especies endémicas registrada hace del Alto Balsas un área prioritaria para la conservación a escala global (Arizmendi, 2002;Bertelli et al, 2017; Navarro-Sigüenza y Peterson, 2004;Peterson y Navarro-Sigüenza, 2000). En términos históricos, la evolución de endemismos en los bosques tropicales secos del occidente de México se explica por varios factores: el efecto de aislamiento que la Faja Volcánica Transmexicana y la sierra Madre del Sur producen sobre la cuenca del Balsas (Becerra, 2005;Morrone, 2014); el levantamiento del istmo de Tehuantepec durante el Mioceno (Mason et al, 2018;Navarro-Sigüenza et al, 2017) y los cambios paleoclimáticos derivados del avance y retroceso de glaciares del Pleistoceno (Arbeláez-Cortés, Milá et al, 2014;Arbeláez-Cortés, Roldán-Piña et al, 2014;Montaño-Rendón et al, 2015;Navarro-Sigüenza et al, 2017). En conjunto, estos procesos moldearon la distribución de los bosques templados y tropicales, generando efectos de aislamiento y contacto periódicos que elevaron las tasas de diversificación de las aves (Lovette, 2005).…”
Section: Discussionunclassified